PENGUJIAN PENGHAMBATAN AKTIVITAS MAKAN DARI EKSTRAK DAUN Lantana camara L. (Verbenaceae) TERHADAP LARVA Plutella xylostella L. (Lepidoptera: Yponomeutidae) - Khaidir Hendrival (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
Research on antifeedant activity of n-hexane leaf extract Lantana camara and its active fractions were evaluated for their insecticidal activity against Plutella xylostella larvae. The method included extraction, fractionation, and examination antifeedant leaf extract L. camara and fractions active against P. xylostella larvae. Extract application was conducted using a residue feeding method. Fractionation of active compounds from extract n-hexane was conducted by liquid vacuum chromatography, using phase silent silicate gel GF254 and phase mobility n-hexane, ethyl acetate, and methanol (elusion gradient), which produce fractions A, B, C, D, and E. Extract leaf L. camara and fractions possessed antifeedant activity against P. xylostella larvae. Extract leaf L. camara at concentration of 1% caused larva antifeedant activity up to 78.47%. Fraction E caused a higher larva antifeedant activity (85,52%) than extract and other fractions did.